Implementasi Sistem Informasi Akuntansi pada PT.Tridika Putra Unggul Tangerang Menggunakan Zahir Accounting Versi 5.1 - Ahmad Yani; Mega S P (Artikel Ilmiah Sistem Informasi Akuntansi, 2021)
Abstract - The development of technology and information systems in the industrial world requires a company to be able to use technology to support the operational activities of the industry. With various advantages of technology and the development of information systems, of course, it can improve the company's performance to produce useful and accurate information for interested parties in making current or future decisions. One of the most important information systems in a company is an accounting information system that will produce financial information. PT. Tridika Putra Unggul Tangerang, which is engaged in the distribution of lubricating oil. Every day the company makes transactions such as buying goods from suppliers and sending goods to customers. PT. Tridika Putra Unggul Tangerang has been computerized using journal software. However, PT. Tridika Putra Unggul Tangerang experienced several problems in recording its transactions, which may result in errors in inputting a transaction into the software and slowing down work such as frequent system updates in using the software. What is often problematic is that journal software cannot make financial reports automatically accurately so that related parties must record manually. Zahir Accounting version 5.1 is an Accounting Information System application that can be a solution to these problems that can help more effectively process transaction data to produce company financial reports. Keywords: Implementation, Accounting Information System, Zahir Application